Postfazione a Penombre acustiche nella matematica esatta del ritmo. Riflessioni su La dialectique de la durée di Gaston Bachelard (2006) - Serra, Carlo (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
What is the relation between the Platonic conception of rhythm as a movement that preserves tension, and Gaston Bachelard’s stratification of crystallized durations, which he reconstructs in his analysis and discussion of the fluent character of Bergsonian duration? Answering this question requires research on the metaphysics of rhythm and how a narrative supported by scanning operates on sound’s matter, on the forms within which it is inscribed and reorganized. The theme of rhythm is a privileged way of examining how Bachelard’s reflection deals with temporal form, and with the metamorphoses that activate a cyclical movement that creates a bridge stretching from the plane of life reflected in consciousness to the construction of a conceptual system that discretizes the flow, while maintaining its narrative tension. It is not surprising that this articulated reflection, featured in La dialectique de la durée (1936), found more resonance in musical theory than in twentieth-century philosophical speculation. This study, conceived in 2006 and rethought today, tries to identify some more conceptually dense themes that await being tackled in a broader study that is focused on rereading temporal healing forms. Through his novel approach, Bachelard manages to reconcile temporal discretion and movement. Keywords: Rythmos, Duration – Scanning shapes, Dialectic, Continuous – Moderate, Melody.